Waveform inversion of acoustic waves for explosion yield estimation. Issue 13 (8th July 2016) - Kim, K.; Rodgers, A.
Abstract: We present a new waveform inversion technique to estimate the energy of near‐surface explosions using atmospheric acoustic waves. Conventional methods often employ air blast models based on a homogeneous atmosphere, where the acoustic wave propagation effects (e.g., refraction and diffraction) are not taken into account, and therefore, their accuracy decreases with increasing source‐receiver distance. In this study, three‐dimensional acoustic simulations are performed with a finite difference method in realistic atmospheres and topography, and the modeled acoustic Green's functions are incorporated into the waveform inversion for the acoustic source time functions. The strength of the acoustic source is related to explosion yield based on a standard air blast model. The technique was applied to local explosions (<10 km) and provided reasonable yield estimates (<∼30% error) in the presence of realistic topography and atmospheric structure. The presented method can be extended to explosions recorded at far distance provided proper meteorological specifications. Key Points: Yield estimation of a near‐surface explosion using acoustic waves Full waveform inversion of acoustic signals incorporating 3‐D numerical modelings Full 3‐D simulation of acoustic waves taking into account topographic and atmospheric propagation effects